The Diverse Roles of Histone Demethylase KDM4B in Normal and Cancer Development and Progression - Wang, Zhongze; Cai, Huarui; Zhao, Erhu; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2022)
Histone methylation status is an important process associated with cell growth, survival, differentiation and gene expression in human diseases. As a member of the KDM4 family, KDM4B specifically targets H1.4K26, H3K9, H3K36 and H4K20, which affects both histone methylation and gene expression. Therefore, KDM4B is often regarded as a key intermediate protein in cellular pathways that plays an important role in growth and development as well as organ differentiation. However, KDM4B is broadly defined as an oncoprotein that plays key roles in processes related to tumorigenesis, including cell proliferation, cell survival, metastasis and so on. In this review, we discuss the diverse roles of KDM4B in contributing to cancer progression and normal developmental processes. Furthermore, we focus on recent studies highlighting the oncogenic functions of KDM4B in various kinds of cancers, which may be a novel therapeutic target for cancer treatment. We also provide a relatively complete report of the progress of research related to KDM4B inhibitors and discuss their potential as therapeutic agents for overcoming cancer.